Third Five Year Plan 1961-62 Progress Report Madhya Pradesh - Planning Commission (Planning Commission, 1961)
The highlights of the agro-economic situation prevailing in the State during the period under review as compared with previous year were considerable increases in the output of two important cereals, viz., rice and wheat which recorded a perceptible increase over previous year’s levels; significant rise in industrial production; mixed trends in the wholesale prices of agricultural commodities, satisfactory condition of labour both in agriculture and industry and perceptible expansion of employment opportunities.
Madhya Pradesh